Ethical and legal duty of anesthesiologists regarding Jehovah's Witness patient: care protocol - Takaschima,Augusto Key Karazawa (2016)
Abstract Background and objectives: Jehovah's Witnesses patients refuse blood transfusions for religious reasons. Anesthesiologists must master specific legal knowledge to provide care to these patients. Understanding how the Law and the Federal Council of Medicine treat this issue is critical to know how to act in this context. The aim of this paper was to establish a treatment protocol for the Jehovah's Witness patient with emphasis on ethical and legal duty of the anesthesiologist. Content: The article analyzes the Constitution, Criminal Code, resolutions of the Federal Council of Medicine, opinions, and jurisprudence to understand the limits of the conflict between the autonomy of will of Jehovah's Witnesses to refuse transfusion and the physician's duty to provide the transfusion. Based on this evidence, a care protocol is suggested. Conclusions: The Federal Council of Medicine resolution 1021/1980, the penal code Article 135, which classifies denial of care as a crime and the Supreme Court decision on the HC 268,459/SP process imposes on the physician the obligation of blood transfusion when life is threatened. The patient's or guardian's consent is not necessary, as the autonomy of will manifestation of the Jehovah's Witness patient refusing blood transfusion for himself and relatives, even in emergencies, is no not forbidden.